Próba uogólnienia metryki Minkowskiego na płaszczyźnie - Biernacki, Marek (An attempt of generalization of Minkowski's metrix on plane, 2005)
In this article Minkowski’s metrix is made generalized by the way of grounding the power that depends upon the absolute remainder of the distance between the coordinates. Given here is an example of inconstant power which this function is a metrix for and of a funktion that has convex layers and that does not comply with the triangle’s condition.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 336-343